Luminescent smart labels for the new generation of optical sensing and Internet of Things - Ramalho, João Filipe Candeias Baptista (2022)
Sensors play a key role on the Internet of Things (IoT) providing monitoring inside and outside the communication networks in a multitude of parameters. Challenges towards IoT lie in the lack of affordable strategies able to convert sustainably, a signal from an optical sensors network into a digital data sequence. The coupling of optical sensors to smartphones appears as an exciting strategy for the new generation of mobile optical (mOptical) sensing. Among optical features, luminescence stands out as a non-invasive spectroscopic method based on the dependence of the phosphor emission on the measurand (e.g., temperature, pH, UV-C dose) which often is translated into color variation easily accessed by the smartphone camera. The intrinsic characteristics of the intra-4f transitions of lanthanide ions (Ln³⁺) provide color purity and tuneability required for image-based sensing. The judicious choice of the ligands and the host for the Ln³⁺ enables the flexible processing in shape, size, and methodology permitting the design of IoT enabling smart labels ensuring authenticity (combining anti-counterfeiting and uniqueness), and traceability. Moreover, the radiation harvesting, and the large Stokes shift provided by the ligands are fundamental to ensure efficient Ln³⁺emission under the lower-excitation powers typical of commercial light-emitting diodes (LEDs). Those aspects predict broad applications ranging, in which, healthcare services standout and the concepts of eHealth and mHealth (mobile-assisted eHealth) arose, being more and more explored towards the development of effective low-cost and sustainable systems that promote healthcare provision. The combined use of smartphones and LEDs is a sustainable approach to the industry and societal acceptance and widespread use, transforming. A new path for advances in photonics research is traced established by the incorporation of smartphones as a tool in science and engineering, foreseeing new designs for mOptical sensors towards IoT.